PAULO FREIRE AND THE PEDAGOGY OF THE OPPRESSED - Ocampo Lopez, Javier (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
This study is a vision on the ideas of the Brazilian educator Paulo Freire (1921-1997), one of the great Latin American educators of the twentieth century. Its aim is to bring the ideas of Freire on the political nature of the problem of education and the need to create a popular school in the Latin American context. He raised a movement on based education, which has been called « Freire’s Method « about pedagogy of liberation, which centralized his educational ideas on his book «Pedagogy of the Oppressed.» Through literacy and popular education, the Brazilian pedagogue pointed out the importance of creating a collective consciousness in the masses about their reality and the need of a pedagogy of liberation to get social justice.